Development of Rice Mutants with Enhanced Resilience to Drought Stress and Their Evaluation by Lab Assay, Field, and Multivariate Analysis - Shahwar Fatima; Muhammad Rashid; Amjad Hameed (Scientifica)
Drought is one of the foremost devastating abiotic stresses reported for rice crops. To improve the productivity of rice, diversity is being enlarged by induced mutation using a source of gamma rays. But this type of mutation rarely results in fruitful products because the chances of getting the desired mutant are very low. The present study aimed to evaluate the rice mutants against drought or osmotic stress. In this study, three experiments were conducted that comprised of seventy-one mutants originating from different doses of gamma rays (Cs137) along with parent RICF-160 and commercial variety (Kainat) were tested. In the first experiment, germination and seedling attributes were calculated under control and osmotic stress conditions created by using 16% (0.6 MPa) polyethylene glycol (PEG-6000). Results revealed that all the mutants exhibited significant (p<0.01) responses to PEG-induced osmotic stress. Principal component biplot analysis (PCBA) revealed the first seventeen cumulative PCs with eigenvalues >1 contributed 88%. It was noted that the germination percentage (GP), germination rate (GR), coefficient velocity of germination (CVG), and seed vigor (SV) contributed maximum and positively in PC1. Results showed the highest germination percentage (GP) at 48 hrs in mutant NMSF-11 (88.9%) followed by NMSf-38 (73.3%). Similarly, the germination rate (GR) and coefficient velocity of germination (CVG) were measured highest in NMSF-11 (9.7 and 118.1%), respectively. In stress conditions, the mutants NMSF-35 and NMSF-36 depicted the highest GP, GR, and CVG. The maximum seed vigor (SV), shoot length (SL), root length (RL), and fresh weight (FW) were observed in mutants NMSF-50 and NMSF-51 under both conditions, whereas the mutants NMSF-59, NMSF-60, NMSF-64, and NMSF-67 showed lower values for SV, SL, RL, and FW. In the second experiment, a field trial was conducted at the Nuclear Institute for Agriculture and Biology (NIAB), Faisalabad, in two control and stress sets. A bit different trend was observed among all mutants for agronomic parameters under both conditions. In the third experiment, biochemical profiling was done in Marker Assisted Breeding (MAB) Lab-1, Plant Breeding and Genetics Division. A significant variation was seen in enzymatic antioxidants and chlorophyll content in both control and stress conditions. Under control conditions, the ascorbate peroxidase (APX) content was observed higher in mutant NMSF-49 (106.07 Units/g. f. wt.). In comparison with the stress, the ascorbate peroxidase activity was higher in NMSF-41 (82.34 Units/g. f. wt.). Catalase (CAT) activity was observed maximum in NMSF-29 (17.54 Units/g. f. wt.) and NMSF-40 (14.17 Units/g. f. wt.) under control and stress conditions, respectively. Peroxidase (POD) activity was observed maximum in NMSF-51 (22.55 Units/g. f. wt. and 10.84 Units/g. f. wt.) under control and stress conditions, respectively. In conclusion, to fit in the changing climate conditions for resilient rice crop production, the promising mutant lines may be used to transfer the desirable drought-tolerant/drought-resistant genes in rice germplasm.